Evaluation of Colonic Perfusion for Colorectal Cancer Surgery Using Indocyanine Green Fluorescence Imaging - TOMIKI, YUICHI; SUGIMOTO, KIICHI; MUNAKATA, SHINYA; ISHIYAMA, SHUN; KOJIMA, YUTAKA; MOTEGI, SHUNSUKE; TAKEHARA, KAZUHIRO; TAKAHASHI, MAKOTO; SAKAMOTO, KAZUHIRO; KAWANO, SHINGO (Juntendo Iji Zasshi = Juntendo Medical Journal, 2021)
Objective: Anastomotic leakage (AL) is one of the most serious postoperative complications in colorectal surgery. AL reportedly occurs in 5-10% of cases following colorectal surgery. Poor colonic perfusion is proceeded to be AL during mesenteric resection. The purpose of this study was to evaluate the clinical utility of assessing colonic perfusion with indocyanine green (ICG) fluorescence imaging.Materials and Methods: The subjects comprised 47 patients who underwent colorectal surgery with double-stapling technique anastomosis between March 2015 and September 2016. We measured the time fluorescence first appeared after the ICG injection and the time until maximum fluorescence was measured. These were compared with other clinical findings that correlated with AL.Results: The median first fluorescence time was 43 sec, and the median maximum fluorescence time was 92 sec. Based on the fluorescence imaging, the surgical team judged the proximal colon to be anastomosed insufficiently in 10 patients (21.2%). The median proximal change distance of the transection line was 12.5 mm (5-70). In all 47 patients, AL occurred in 6 patients (12.8%). Maximum fluorescence time (over 98 sec) was significantly longer in the AL group (p=0.025).Conclusions: The results of this study suggested that assessing colonic perfusion using ICG fluorescence imaging during colorectal surgery was clinical useful. It was considered that patients with elongation of fluorescence time should be careful of AL.